(untitled) (Biological Sciences - PJSIR, 2007)
Concentrations of pol ych lori natcd bi phen yls (PCBs) a nd organoch lori ne pesticid es (OCPs) i n c l ud i n g IDDTs, Ich lordanes, IBHCs, dield ri n , heptach l or epoxide etc were measu red i n the tissues of di fferent sh e l l fishes and flou nder eggs of Ri ver James at Vi rgi n ia Coast, USA. PCBs were th e most predomi nant contam i n ants, fol l owed by Ich lordanes, IB!-1 Cs, IDDTs, and other OCPs. Concentration of OCPs decreased by an order of magn i tude during the l ast decades i n th is region; nevertheless, the concentration of PCBs and OCPs i n sh el l fishes arc sti l l elevated. Concen trations of organoch lori nes were h igh ly correl ated wi th one another, and were in the range of a few to several ng/ g on a wet wei ght basis. I n the tissue of sh e l l fishes, th e sum of IOCPs ranged from 1 93.5-665.53 ng/ g, predom i nated by Ich lordanes. IPCB h ad an overal l range of 287. 7-28207.9 ng/g and were pred omi n ated by IAroc l or 1 248.